EPR and DRS evidence for NO2 sensing in Al-doped ZnO - Navale, Shalaka C.; Ravi, V.; Srinivas, D.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2008)
Zinc oxide (ZnO) is a well-known semiconducting multifunctional material wherein properties right from the morphology to gas sensitivity can be tailor-made by doping or surface modification. Aluminum (Al)-incorporated porous zinc oxide (AI:ZnO) exhibits good response towards NO2 at low-operating temperature. The NO2 gas concentration as low as 20 ppm exhibits S = 17% for 5 wt. % Al-incorporated ZnO. The NO2 response increases with operating temperature and concentration and reaches to its maximum at 300 degrees C without any interference from other gases such as SO3, HCl, LPG and alcohol. Physico-chemical characterization likes differential thermogravimetric analysis (TG-DTA) electron paramagnetic resonance (EPR) and diffused reflectance spectroscopy (DRS) have been used to understand the sensing behavior for pure and A]-incorporated ZnO. The TG-DTA depicts formation of ZnO phase at 287 degrees C. The EPR study reveals distinct variation for O- (g=2.003) and Zn interstitial (g = 1.98) defect sites in pure and Al:ZnO. The DRS studies elucidate signature of adsorbed NO, species in aluminium-incorporated zinc oxide indicating its tendency to adsorb these species even at low temperatures. This paper is an attempt to correlate the gas sensing behavior with the physico-chemical studies such as EPR and DRS. (c) 2007 Published by Elsevier B.V.
Keywords: aluminum doping; DRS; EPR; NO2 sensor; ZnO